FROM PROPHETIC LEADERSHIP TO SUSTAINABLE COMMUNITY DEVELOPMENT: CONTRIBUTING KIAI NAJIB SALIMI IN CONTEMPORARY PESANTREN - Ahmad Izudin (al-Balagh : Jurnal Dakwah dan Komunikasi, 2021)
Kiai is highlighted as a difficult (to reach) figure because of social class classification that lives in the public consciousness. Despite the kiai is considered to have a high social class, this does not make the kiai forget its social role. In this case, it can be referredto Kiai Najib Salimi as the founder of the Luqmaniyah pesantren. This paper aims to explore the contribution of Kiai Najib Salimi in community development and the factors behind it based on prophetic values. The study employed a qualitative method with a biographical approach. Data were collected via document searches, interviews, and observations. It was revealed that the Kiai had transformed into founders pesantren and developed into changes makers, social planners, and social facilitators. The contribution of Kiai Najib Salimi was exposed in the establisment of Luqmaniyah pesantren, Micro-finance (Koperasi) Kodesmata, Ngrowot fasting, and the Syuri’ah of Nahdlatul Ulama in Yogyakarta City. This paper also features that the impetus for taking empowerment is personal factors, family, educational pesantren, and social environment. In fact, the contribution made by Kiai Najib Salimi holds ethical values in the practice of community empowerment. This finding, by implication, requires only further action that prophetic values are not based on ethical concepts, but must contribute practically to social life.